Morpho-Ecological Features Of Pikeperch (Stizostedion Lucioperca) In Lakes Of Ayakagytma In Uzbekistan (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study presents the morpho-ecological features of pike perch fish in the conditions of Ayakagytma Lake. It described that a comparative analysis of growth and morphometry between Ayakagytma and Dengizkul fishes. Also, it is informed on the nutrient content and fertility of pike-perch in Ayakogytma Lake..